Cytogenetic analysis of five species of the subfamily Corydoradinae (Teleostei: Siluriformes: Callichthyidae) - Shimabukuro-Dias, Cristiane Kioko [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Sociedade Brasileira de Genética, 2004)
In the present study, five callichthyid species belonging to the subfamily Corydoradinae were karyotyped: three species of Aspidoras and two of Corydoras. The three species of Aspidoras had the same diploid number, 2n = 46 chromosomes, similar karyotypic formulae, with most chromosomes metacentric or submetacentric, single interstitial Ag-NORs and C-band positive segments mainly found in the centromeric position. The comparative analysis of cytogenetic data available for the genus Aspidoras and other species of Corydoradinae suggest that several events of centric fusion occurred in the origin of the species of Aspidoras. The two analyzed species of Corydoras showed high diploid numbers, 2n = 74 in C. sodalis and 2n = 90 in C. britskii. While C. sodalis exhibited single Ag-NORs and terminal, interstitial and centromeric C-band positive segments in almost all chromosomes, C. britskii showed multiple Ag-NORs and a small number of C-band positive segments found in the terminal position in one acrocentric (A) pair and in the interstitial position in one subtelocentric (ST) pair. The occurrence of high diploid numbers and many ST and A chromosomes are uncommon among the Corydoradinae, suggesting the occurrence of a high number of chromosome rearrangements, mainly centric fissions, in the origin of the Corydoras species studied.
Keywords: fish cytogenetic; karyotype; NOR; C-banding; karyotypic evolution